A Discourse Analysis Of Newspaper Leads In The Jakarta Post Using Frame Theory - Haristmawan, Indra; , Dra. Malikatul Laila, M.Hum; , Drs. Djoko Srijono, M. Hum (2013)
This research paper is aimed to identify frame elements to configure the discourse of newspaper leads in The Jakarta Post newspaper. The data of this study are in the form of written discourse of newspaper leads in The Jakarta Post newspaper which includes expression of words. There are 5 written discourse used as the data that are collected through observation and document the data. The collected data are then analyzed using Gamson and Modigliani theory to identify frame elements to configure the discourse of newspaper leads in The Jakarta Post newspaper. The result of this study has shown that the frame elements to configure the discourse of newspaper leads are 5 metaphors, 5 catchphrases, 5exemplar, 5 the depictions, 1 visual images, 5 the euphemism, 5 the roots, 5 the appeal to principle.